1999
DOI: 10.1111/j.1540-8167.1999.tb00706.x
|View full text |Cite
|
Sign up to set email alerts
|

The Activation of Platelet Function, Coagulation, and Fibrinolysis during Radiofrequency Catheter Ablation in Heparinized Patients

Abstract: Procedure duration prior to heparin administration, and not the delivery of RF current per se, determines activation of hemostasis and fibrinolysis during RF ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 26 publications
4
30
0
3
Order By: Relevance
“…The hemostasis that occurs with the placement of catheters has been described, 6,7,16,17 with some investigators correlating it with the duration of the pre-heparin procedure, as was seen in the present study. 7 Another report showed that platelet aggregability increased during RF current delivery, 9 and Manolis et al showed that RF-CA provoked an elevation in the D-dimer concentration by 48 h after the procedure.…”
Section: Thrombogenesis Caused By Radiofrequency Currentsupporting
confidence: 55%
See 2 more Smart Citations
“…The hemostasis that occurs with the placement of catheters has been described, 6,7,16,17 with some investigators correlating it with the duration of the pre-heparin procedure, as was seen in the present study. 7 Another report showed that platelet aggregability increased during RF current delivery, 9 and Manolis et al showed that RF-CA provoked an elevation in the D-dimer concentration by 48 h after the procedure.…”
Section: Thrombogenesis Caused By Radiofrequency Currentsupporting
confidence: 55%
“…7 Another report showed that platelet aggregability increased during RF current delivery, 9 and Manolis et al showed that RF-CA provoked an elevation in the D-dimer concentration by 48 h after the procedure. 8 These previous studies have not fully elucidated the influence of the RF current on thrombus formation nor have they observed the delayed phase of thrombogenesis.…”
Section: Thrombogenesis Caused By Radiofrequency Currentmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefit of heparinization administration during catheter ablation procedures is unclear, with several reports demonstrating either no benefit or no enhanced benefit with earlier heparin administration after placement of sheaths. 544,556,557 Epstein et al 558 demonstrated a low incidence of embolic complications among 758 pediatric and congenital patients from 11 centers. A wide variety of anticoagulation protocols was used, but all used heparin for left-side ablations.…”
Section: Anticoagulation and Catheter Ablation Proceduresmentioning
confidence: 99%
“…Gillinov and colleagues, 34) and Mohr and colleagues 35) reported esophageal injuries associated with unipolar RF ablation, and microembolization and hemostatic activation in percutaneous RF catheter ablation were reported by Anfinsen and colleagues, 36) and Kok and colleagues. 37) Since it is possible that such complications occur in the Maze procedure, we minimize the blood around the RF probe and routinely irrigate the left atrium with saline solution after RF ablation in order to wash out char.…”
Section: Discussionmentioning
confidence: 99%